Perspective—Historical Roots of theA Behavioral Theory of the FirmModel at GSIA - Augier, Mie; Prietula, Michael (Organization Science, 2007)
Richard Cyert and James March’s (1963) A Behavioral Theory of the Firm (ABTOF) is one of the most influential works in organization science. An important element of that work was a computational model of a duopoly, which was arguably the first computational model that instantiated organizational constructs within a substantial theoretical framework. We suggest that the academic environment within which this theory and model grew was instrumental in its emergence. Furthermore, an examination of the model itself (by triangulating on the verbal descriptions, the flow charts, and the code) reveals innovative embodiments of organizational attention, organizational learning, organizational memory, routines, metaroutines, aspiration level adjustments and computational experiments. In this paper we examine the historical roots of the model—the concepts, culture, and characters at Carnegie Tech and the Graduate School of Industrial Administration (GSIA). Although causality is difficult to assess historically, we suggest the significance of a strong research-based, interdisciplinary culture at a time when innovative (and often computational) concepts and theories were emerging within the contexts of computer science, economics, and psychology.